Impact of land use on water quality of sungai Kenyana and its tributaries in Mukah, Sarawak - Dayang Farhanna, Awang Bolhasan (Universiti Malaysia Sarawak, (UNIMAS), 2014)
A study was conducted in Sg. Kenyana and its tributaries, Mukah, Sarawak, a peat swamp river in order to determine the impact of land use on water quality in the river. This area has a great potential for eco-tourism and it also plays important roles as natural habitat for Asian Arowana. However, the influence of big scale oil palm plantation which also includes huge area of land clearing activities has change the natural condition of the rive;) In-situ data and water samples were collected at six sampling stations from 15th until 18 th rv6rch 2013. In-situ data included pH, temperature, Dissolved Oxygen (DO) and turbidity. Analysis for Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Suspended Solids (TSS), ammoniacal nitrogen (NH3-N), nitrate (N03-N), orthophosphate (P04 3-), Total Coliform Counts (TCC) and Faecal Coliform Counts (FCC) were conducted in the laboratory. The range values of water quality parameters obtained are as follows: pH (4.36 - 5.87), temperature (28.13 - 28.57 DC), turbidity (35.8 - 95.0 NTU), Do (0.08 - 4.32 mglL), COD (40.5 - 70.4 mg/L), BOD (1.21 - L90 mglL), TSS (24.23 - 56.44 mglL), ammoniacal nitrogen (0.490 1.261 mg/L), nitrate (0.1 - 0.2 mg/L), orthophosphate (0.036 - 0.1 05 mg/L), TCC (l,028 2,750 count/IOO mL) and FCC (333 - 1,111 count/l 00 mL). Overall, the results show that the physical-chemical parameters of water in Sg. Kenyana were in normal range (Class I and II) except for DO, ammoniacal nitrogen, FCC and turbidity (Class III - moderate) and COD and pH (Class IV - bad). However, the low values of pH and DO are normal for peat water (black water). The Water Quality Index (wQI) was calculated to determine the state of water quality in Sg. Kenyana. Based on WQI, Sg. Liwak was categorised under Class IV while Sg. Kenyana and Btg. Mukah were categorised under Class III. Out of six physicochemical parameters of water in Sg. Kenyana that are required for WQI calculation, four of them were in Class III and IV (PH, DO, COD, and ammoniacal nitrogen) while the other two were in Class I and II (BOD and TSS).